EFFECT OF WATER SATURATION ON STABILITY OF A HILL SLOPE: MALIN CASE STUDY - Prashant Sudani; Kailas Patil (Advances in Civil and Architectural Engineering, 2023)
The study presents a meticulous investigation into the catastrophic landslide that impacted Malin village in Pune district of Maharashtra, India. By employing a multi-faceted approach encompassing field, laboratory, and numerical analyses, in the study, stability governing parameters were thoroughly assessed with respect to varying levels of water saturation. Field investigation provided crucial insights into the geographical profile, field density, slope strata, and representative soil sample acquired from hill slopes. Furthermore, extensive laboratory investigations were conducted to gain a comprehensive understanding of the role of stability governing parameters under different water saturation levels. The limit equilibrium method was employed for numerical simulation to rigorously evaluate slope stability. The results revealed the significant influence of increased water saturation on stability governing parameters, leading to slope instability, which was confirmed by numerical simulation. The study further established that excessive rainfall triggered the landslide, saturating the soil mass and deteriorating the stability governing parameters, ultimately leading to instability. The findings of this study offer valuable insights for mitigating landslides and can be instrumental in developing effective monitoring and warning systems.